Acute intestinal obstruction in Peutz Jeghers syndrome: a case report - Anuragi, Gajendra; Bagwan, Afroz I.; V. S., Ramprakash; C., Sugumar; Lakshmanamoorthy, Naganath B. O. (International Surgery Journal, 2021)
Peutz Jeghers syndrome is an autosomal dominant hereditary disorder affecting male and female equally. It is characterised by mucocutaneous hyperpigmentation and hamartomatous polyp in gastrointestinal tract with increased risk of malignancy. We report here a case of 52-year-old patient with traits of Peutz jeghers syndrome presented with acute intestinal obstruction following colocolic intussusception. Peutz jeghers syndrome is an autosomal dominant inherited disorder. Individual may present in rare case with acute intestinal obstruction associated with intussusception due to polyps.